Diverse Coordinative Zinc Complexes Containing Amido-Pyridinate Ligands: Structural and Catalytic Studies - Chen, Ming-Tsz; Chen, Yu-Yang; Li, Guan-Lin; Chen, Chi-Tien (Frontiers in Chemistry, 2019)
In this work, zinc complexes containing amido-pyridinate ligands substituted with different pendant arms have been described. Treatment of ligand precursors with ZnEt2 in 1:1 ratio in THF yields zinc ethyl complexes, (PyNC1Py)2(ZnEt)2 (1) and (PyNC2NMe2)2(ZnEt)2 (2), respectively. Complexes 1 and 2 show the same geometry as a distorted tetrahedron but adopt different coordinative behaviors supported by the ligands. Complex 1 represents a rare and a non-centrosymmetric mode which the amido group bridges two zinc centres to form a six-membered ring, however complex 2 shows a centrosymmetric mode which the pyridine group links the zinc centres to form an eight-membered ring. Recrystallization of complex 2 gives an additional complex (PyNC2NMe2)4Zn3(μ3-O) (3). Attempt to prepare zinc benzyl oxide complexes affords a self-assembly cubane complex Zn7Et6(OBn)8 (4). All molecular structures 1-4 are identified by single crystal X-ray as well as spectroscopic data. Furthermore, their catalytic studies toward the ring opening polymerization of ε-caprolactone and L-lactide in the presence of benzyl alcohol are investigated.